Armenian – Mamluks Relations - Fatma; AKKUŞ YİĞİT (Gazi Akademik Bakış)
Armenians, were able to establish a state on their behalf in consequence of the Crusades and do not miss the great historical opportunity, in Cilicia (Çukurova). Armenian Kingdom of Cilicia in the vicinity of Cukurova have been fed with the support of the Crusader States and Cyprus, and especially after being subjected to the Il-Khans in their regions had reached a certain strength. However, the Armenians, they apply their attacks and with trade embargoes, they were made themselves the target of the Mamluk State. By the capacity of a single state to stop the Mongols in the region, proved the power of the Mamluks, and it was not possible to remain silent this situation. From 1260, the Armenian capital, Sis, reduced date that until 1375 the period of time, as a result of political, struggle, almost continuous-time war between Mamluks and the Armenians, Mamluk had been the empire continue to existing side, In this study, 115 years of laying down the Mamluk-Armenian relations, will be presented with detailed information about the subject.